(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
One of the main tasks and objectives of applied linguistics is to determine the place of language and its forms of expression in a literary text, which encompasses multifaceted processes. In this context, an analysis of the place of speech formations, including phonopoeic devices, in a literary text is also relevant, using the vocabulary of a particular poet’s poetry as an example. After all, determining the lingua-poetic potential of linguistic devices requires reliance on literary texts and an analysis of the works of a number of poets and writers. Studying the language of a work of fiction is a complex process. It encompasses not only literary theory concepts such as artistic idea, plot, imagery, individuality, and the author’s artistic skill, but also linguistic ones such as pragmatics, semiotics, and connotation. It is linked to such scientific fields as cognitive linguistics and sociolinguistics.